PENGARUH LITERASI KEUANGAN DAN PENGENDALIAN DIRI TERHADAP PERILAKU PENGELOLAAN KEUANGAN (Survei Pada Tenaga Pendidik SD Se-Kecamatan Kuningan) - Komarudin, Munir Nur Komarudin; Nugraha, Nugraha; Hardjadi, Dikdik; Pasha, Riska Ayu (Jurnal Keuangan dan Bisnis, 2020)
The purpose of this study to determine the influence of financial literacy and self-control on financial management behavior conducted a survey of elementary school teacher educators in Kuningan District. The study population was 56 people. The method of determining the sample using a saturation sampling method with a sample followed the population as much as a total sample of 56 people. The data analysis technique using regression analysis. Based on the results of the study stated that Financial Literacy has a positive and significant effect on financial management behavior and self-control has a positive and significant effect on financial management behavior.